Estimación de la huella hídrica agrícola del DR 011, alto río Lerma - Botello-Aguillón, César; Valdivia Alcalá, Ramón; Sangerma Jarquín, Dora Maria de Jesús; Hernández Ortiz, Juan; Gutiérrez García, Francisco Gerardo; Sandoval Romero, Fermín (Revista Mexicana de Ciencias Agrícolas, 2024)
In the search for indicators that help measure the impact of human activities on the environment and natural resources, there is one that is very useful as an indicator of demand for global water resources. Estimating the water footprint of agricultural production allowed the identification of crops that can reduce it in favor of increasing water use efficiency. Hoekstra et al. (2011) methodology was used to estimate the water footprint of agricultural products in Irrigation District 011. It was found that of 14 crops in the district, in the average total water footprint in the irrigation modules (dam3 t-1), those of peanuts, beans, and nopal report the highest levels (1.7, 1.6, and 1.8, respectively), while those of lettuce, husk tomato, and carrot crops are the lowest (0.15, 0.29, and 0.25, respectively). Of the water footprint of total agricultural production (dam3), it was observed that corn participates with 43.4%; however, it accounted for 52.8% of total production. The peanut and alfalfa crops in module 05 are economically unaffordable, with high blue water costs per tonne (8 623.00 and 11 914.00); nevertheless, they occupy 1% of the planted area. The variation of the water footprint of crops among the irrigation modules obtained helps identify the agricultural practices that contributed to increasing yields and optimizing the application of irrigation, consequently providing greater economic benefits to producers.